Tussen mentors en minnaars: ŉ Voorstel vir ŉ nuwe leesmodel vir die lees van werke deur skrywers soos Peter Blum en lna Rousseau, waar ŉ persoonlike verhouding tussen die skrywers bestaan het - Colyn, Tania (Afrikaans and Netherlandic Studies, 2017)
This study investigates the problematic nature of personal relationships between certain writers and seeks to understand the nature of their relationship and the resulting influence on their work. The question of intellectual property rights is also raised - when two writers live together and discuss their ideas with one another, who owns the final text? Both feminism and psychoanalysis are used to investigate the relationships between the various writers. The work of Sigmund Freud and Carl Gustav Jung especially is used as basis for analysis. A modern lens is used to investigate the relationship between four local writers - the first example is the relationship between Ina Rousseau and Peter Blum, and the second example the relationship between Sheila Cussons and N.P. Van Wyk Louw. After this, the relationships between international writers are investigated - firstly the relationship between Simone de Beauvoir and Jean-Paul Sartre, and then the relationship between Hélène Cixous and Jacques Derrida is studied. After using the lens of modernism, the focus moves to a post-modernism reading of the work of Hennie Aucamp and Koos Prinsloo, as well as the conversation that originated between these two writers. An investigation of Johann de Lange as a rewriter of their work is also conducted. Aucamp and Prinsloo had a mentor-mentee relationship, but in his work Prinsloo has insinuated that Aucamp was interested in a sexual relationship with him. However, De Lange contextualised this in his work and "corrected" Prinsloo's perception by stating that Aucamp merely intended to mentor Prinsloo and was not interested in any kind of intimate relationship with Prinsloo. Slavoj Žižek's theory is used as a possible solution for the question posed in this study. His work represents a bridge between the modern and post-modern readings of the works studied here. Applying his theory, the study attempts to bridge the gap between modernism and postmodernism. Žižek investigates the nature of the relationship between the viewer/reader and the artwork, as well as the suspension of the borders between fiction and reality. He investigates the fictional space, as well as the interaction of the reader/viewer with this space. Judith Butler's theories regarding gender construction are also used to inform the interpretation.